2019
DOI: 10.3991/ijim.v13i11.10924
|View full text |Cite
|
Sign up to set email alerts
|

Developing A Mobile Web for Innovative University Assessment System: Thailand Talent Mobility Programme

Abstract: <p class="0abstract">Empirical research methods were used to study the Thailand Talent Mobility Programme and critical factors effecting participation in the project; from the perspectives of academic researchers in Science, Technology, and Innovation, in order to strengthen the competitiveness of technological innovation in Thailand. On the basis of questionnaire surveys of 58 universities and 17 research institutes, 613 academic researchers across the country responded the survey. All responses were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Castillo et al (2014) found that the FONTAR program stimulated innovation spillovers through talent mobility. Kongsoontornkijkul et al (2019) mentioned that technological talent brought new innovative thinking and opened up new innovation paths. Moodley (2021) found that knowledge management tools can stimulate innovation through knowledge sharing.…”
Section: The Theoretical Analyses and Hypothesesmentioning
confidence: 99%
“…Castillo et al (2014) found that the FONTAR program stimulated innovation spillovers through talent mobility. Kongsoontornkijkul et al (2019) mentioned that technological talent brought new innovative thinking and opened up new innovation paths. Moodley (2021) found that knowledge management tools can stimulate innovation through knowledge sharing.…”
Section: The Theoretical Analyses and Hypothesesmentioning
confidence: 99%
“…We conducted a cluster analysis for building the BDMM through LCA by using the Proc LCA software [49] and R package v.1.4.1 [50]. The number of groups that were tested ranged from three to six, as BDMMs, in general, comprise four-six groups [34].…”
Section: Questionnaire and Validationmentioning
confidence: 99%
“…Many studies investigated users attitude on mobile technology through adoption of tools or consumer application such as mobile banking [44], google translation [45], e-learning in university system [46,47] and mobile commerce adoption via mobile applications [48]. TAM model also used for organization assessment for the evaluate e-commerce assessment for SMEs [49] and university assessment [50] in Thailand. In summary, TAM is the most effective model and can be used as a tool to collect user's comments for improving the system.…”
Section: Tammentioning
confidence: 99%
“…It will start with Matlab Toolbox for IoT applications for event simulation. The reader may also refer to researches like in [12][13][14][15] to engage with mobile services understanding.…”
Section: Fig 2 Systems Frameworkmentioning
confidence: 99%